A feasibility study on the establishment of a local church library for the first free Methodist Church of Manila - Guimary, Jo-ann T. (2006)
Church libraries have been in existence for centuries already but where in the past access had been limited to the clergy, now all members of any the congregation have access to the same materials. The objective of this paper was to determine whether it is feasible to establish a library in the First Free Methodist Church of Manila. Feasibility was determine in three areas: market, technical and organizational, and financial.